Mito e imaginário social: Uma proposta de análise acerca da atuação da DOPS em relação ao PCB no norte do paraná (1945-1953) - Ipólito, Verônica Karina [UNESP] (Universidade Estadual de Ponta Grossa (UEPG), 2014)
The purpose of this work is to analyze the representations of the Bureau of Political and Social Order (DOPS) compared to the actions of militants of the Communist Party of Brazil (PCB) in the northern region of Paraná in the period between the end of the New State regime and the promulgation of theNational Security Act (LSN) in 1953. Being DOPS an organ of social control that takes into account the mechanisms of repression triggered by the state, whose goal was to maintain the established order. In the period from 1945 to 1953 the state of Paraná was branded by the effervescent organization of the rural workers, mainly synthesized by the struggle for land, as it was the case of the War of Porecatu, the Uprising of the Southwest and by a daily political struggle in the cities, be it by political debates by the end of the Second War, the process of legalization of the Brazilian Communist Party and its subsequent proscription or in constant urban social movements. The role of political police in this period is still set for political control, cultural or any form of expression that means a threat to established social order. The research's approach will highlight the political culture emphasizing its role in power relations, taking into account the representations, values , traditions and culture of the social actors involved in the movements. It is the intention of the work, therefore, to demonstrate that the period discussed here was a contradictory period where there was freedom in theory but in practice the power of the State inhibited the rights to decide and act.
Myth and social imaginary: An analysis proposal on the performance of DOPS with regard to PCB in northern paraná (1945-1953)
Keywords: Dops-pr; Pcb; Political culture